IMPROVING BREAST SELF-EXAMINATION (BSE) SKILLS THROUGH ANIMATED VIDEO EDUCATION AMONG FEMALE STUDENTS AT SMAN 5 - Komala Kartikasari Nst; Nelva Riza; Fitria Fitria (Getsempena Health Science Journal, 2025)
In 2020, approximately 2.3 million women worldwide were diagnosed with breast cancer, and 7.8 million women survived within five years after diagnosis, making breast cancer the most common cancer globally. Lack of physical activity and the consumption of fast food are among the main risk factors for breast cancer. Currently, breast cancer also affects younger women. Therefore, increasing knowledge and preventive behavior through health interventions is essential. This study aimed to improving breast self-examination (BSE) through animated video education among female students. This research employed a pre-experimental design with a one-group pre-test post-test design. The population consisted of all 11th-grade female students at SMAN 5 Banda Aceh, with a total sample of 38 students selected by purposive sampling. The study was conducted from January to March 2025. Data were analyzed using the Wilcoxon test. The univariate analysis showed that before the intervention, most students had poor BSE skills (52.6%), while after the intervention, most students demonstrated good BSE skills (63.2%). The bivariate analysis revealed that health education using animated video significantly improved BSE skills (p < 0.05). Based on the findings, it is recommended that students regularly practice BSE once a month as an effort for early detection of breast abnormalities.